Autonomous Learning In Mathematics Statistical Learning Materials For Junior High School Students - Jajang Rahmatudin; Yaya S Kusumah; Bambang Avip Priatna (EduMa: Mathematics education learning and teaching, 2025)
This study investigates students' learning autonomy in mathematics education, recognizing its importance in fostering critical thinking, problem-solving, and lifelong learning skills. A descriptive qualitative method was used to explore the level of independence among junior high school students in Cirebon Regency. The research involved 33 students who completed a learning independence questionnaire consisting of 30 items covering 8 indicators, such as initiative, responsibility, self-regulation, and goal-setting. Data were analyzed using a percentage formula to interpret student responses. The findings show that two indicators scored below the minimum sufficient level, indicating a lack of independence in certain aspects of learning. The remaining indicators met the sufficient criteria. Overall, the average percentage of student learning independence was 64.63%, which falls into the "sufficient" category. In terms of individual classification, 3 students demonstrated good independence, 22 were categorized as sufficient, 6 as poor, and 2 as very poor. These results suggest that while most students show a moderate level of autonomy, there remains a significant need for improvement. Teachers should implement learning strategies that promote self-directed learning and internal motivation to enhance students’ autonomy, particularly in mathematics, where independent learning is key to mastering complex concepts